2022
DOI: 10.1108/cbth-09-2021-0213
|View full text |Cite
|
Sign up to set email alerts
|

Hospitality enterprises’ revival through crowdfunding: a cross-country study

Abstract: Purpose The purpose of this study is to suggest a reward-based crowdfunding approach and test customers’ financial contribution behaviour (FCB) as a fundraising strategy for hospitality enterprises. Design/methodology/approach To investigate this initiative, a conceptual model motivated by the theory of planned behaviour, integrating economic, emotional, social and altruistic values, perceived risk and electronic word of mouth has been considered. Partial least square structural equation modelling is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…This risk assessment will, in turn, lead people to perform actions that can reduce their risk of being infected, for instance, donating money to help the government fight against the pandemic. Similarly, Baber et al (2022) found that people with a higher perceived risk of the COVID-19 pandemic made more financial contributions in crowdfunding. However, risk perception may not always motivate donations when considering the financial side.…”
Section: The Mediating Role Of Risk Perceptionmentioning
confidence: 87%
See 1 more Smart Citation
“…This risk assessment will, in turn, lead people to perform actions that can reduce their risk of being infected, for instance, donating money to help the government fight against the pandemic. Similarly, Baber et al (2022) found that people with a higher perceived risk of the COVID-19 pandemic made more financial contributions in crowdfunding. However, risk perception may not always motivate donations when considering the financial side.…”
Section: The Mediating Role Of Risk Perceptionmentioning
confidence: 87%
“…Since its first onset in late 2019, COVID-19 has led to 6.22 million deaths worldwide during the past 3 years ( Center for Systems Science and Engineering at Johns Hopkins University, 2022 ). During the pandemic, government funding alone is not enough to overcome the healthcare system burden, the massive unemployment, the financial difficulty of hospitality industries and other corporations, and the lack of living necessities ( Baber et al, 2022 ). Donation from the general public plays an important role in mitigating the pressure in different social aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Islamic crowdfunding campaigns are crucial for the hotel industry, which has been adversely affected by the COVID-19 pandemic (Baber et al, 2022). There is a need for better alternatives to enhance crowdfunding trust among donors for strategic sustainability in the conditions of turbulence and financial crisis caused by COVID (Jiao et al, 2022).…”
Section: Crowdfunding and Islamic Financementioning
confidence: 99%
“…Based on Table 6, it can be seen that crowdfunding, fintech, blockchain, fintech, Malaysia, Islamic Finance, and Innovation occupy the 6th largest position in the Islamic crowdfunding document. Crowdfunding is the keyword with the largest number of documents, because crowdfunding campaigns are very important for the hotel industry which is affected by the COVID-19 pandemic (Baber et al, 2022). Factors that influence the success of a crowdfunding campaign include the inherent quality of the project in determining the success of the campaign (Wan Mohamad Nazarie and Williams, 2021).…”
Section: The Most Influential Studies Based On Abstractmentioning
confidence: 99%